PRMT5 Promotes Pancreatic Cancer Tumorigenesis via Positive PRMT5/C‐Myc Feedback Loop - Fan Yang; Ping Song; Zhaofeng Xiao; Renyi Su; Xin Fang; Yichao Wu; Xiao Xu; Kai Wang (MedComm)
ABSTRACT The oncogenic role and underlying mechanism of PRMT5 in pancreatic ductal adenocarcinoma (PAAD) remained to be elucidated. In this study, we aimed to investigate the oncogenic role, underlying molecular mechanisms, and potential therapeutic value of PRMT5 in PAAD. PRMT5 was significantly upregulated in pancreatic cancer than adjacent nontumor pancreas, which was positively correlated with poor prognosis. Genetic and pharmacological inhibition of PRMT5 suppressed PAAD proliferation in vitro and in vivo, exhibiting promising therapeutic effect in vivo. Mechanistically, PRMT5 directly bound to the promoter region of c‐Myc and activated its transcription. Transcriptionally activated c‐Myc in turn inhibited proteasome‐mediated degradation of PRMT5 and enhanced its protein stability, resulting in increased PRMT5 expression. The maintained PRMT5 further enhanced the transcription of c‐Myc. In conclusion, PRMT5 forms a positive feedback loop with c‐Myc to promote the proliferation of pancreatic cancer. Targeting this oncogenic communication may represent a novel and potential therapeutic approach for pancreatic cancer.